2016
DOI: 10.1161/circoutcomes.115.002541
|View full text |Cite
|
Sign up to set email alerts
|

Vancouver Transcatheter Aortic Valve Replacement Clinical Pathway

Abstract: Abstract-We describe the development, implementation, and evaluation of a standardized clinical pathway to facilitate safe discharge home at the earliest time after transfemoral transcatheter aortic valve replacement. Between May 2012 and October 2014, the Heart Team developed a clinical pathway suited to the unique requirements of transfemoral transcatheter aortic valve replacement in contemporary practice. The components included risk-stratified minimalist periprocedure approach, standardized postprocedure c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…Indeed, other groups are evaluating the use of conscious sedation in combination with a care pathway to facilitate next day discharge post TAVR [2931]. Conscious Sedation and non- surgical access have been associated with less delirium and might explain the shorter LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other groups are evaluating the use of conscious sedation in combination with a care pathway to facilitate next day discharge post TAVR [2931]. Conscious Sedation and non- surgical access have been associated with less delirium and might explain the shorter LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Severity of delirium was defined by the delirium observation score [ 26 ]. In case of delirium, patients were treated according to current national guideline ‘Delirium in adults’, Dutch Geriatrics Society [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…24 Single site studies have reported savings of $10,000 to $16,000 for patients treated with a minimalist approach and discharged within shorter LOS without compromising patient safety. [25][26][27] The recent publication of the Multimodality, Multidisciplinary but Minimalist TAVR (3M TAVR) study demonstrated the safety and reproducibility of the Vancouver TAVR Clinical Pathway 23 to facilitate NDD home in over 50% patients screened at 13 TAVR centers of varying procedural volume and program maturity while achieving excellent clinical outcomes. 13 Careful attention to all components of patients' journey of care is essential to consistently achieve similar results.…”
Section: Study Contextmentioning
confidence: 99%